One tool to bring them all: Au-catalyzed synthesis of B, O- and B, N-doped PAHs from boronic and borinic acids. Issue 16 (26th March 2021) - Ouadoudi, Omar; Kaehler, Tanja; Bolte, Michael; Lerner, Hans-Wolfram; Wagner, Matthias
Abstract : Singly and doubly B, E-doped PAHs were synthesized using a protocol that starts from easy-to-handle boronic and borinic acids and offers the possibility to choose between the preparation of B, O- and B, N-PAHs in the final reaction step. Abstract : The isoelectronic replacement of CC bonds with − BN + bonds in polycyclic aromatic hydrocarbons (PAHs) is a widely used tool to prepare novel optoelectronic materials. Far less well explored are corresponding B, O-doped PAHs, although they have a similarly high application potential. We herein report on the modular synthesis of B, N- and B, O-doped PAHs through the [Au(PPh3 )NTf2 ]-catalyzed 6- endo -dig cyclization of BN–H and BO–H bonds across suitably positioned CC bonds in the key step. Readily available, easy-to-handle o -alkynylaryl boronic and borinic acids serve as starting materials, which are either cyclized directly or first converted into the corresponding aminoboranes and then cyclized. The reaction even tolerates bulky mesityl substituents on boron, which later kinetically protect the formed B, N/O-PAHs from hydrolysis or oxidation. Our approach is also applicable for the synthesis of rare doubly B, N/O-doped PAHs. Specifically, we prepared 1, 2-B, E-naphthalenes and -anthracenes, 1, 5-B2 -2, 6-E2 -anthracenes (E = N, O) as well as B, O2 -containing and unprecedented B, N, O-containing phenalenyls. Selected examples of these compounds have been structurally characterized by X-ray crystallography; their optoelectronic properties have been studied by cyclic voltammetry, electron spectroscopy, and quantum-chemical calculations. Using a new unsubstituted (B, O)2 -perylene as the substrate for late-stage functionalization, we finally show that the introduction of two pinacolatoboryl (Bpin) substituents is possible in high yield and with perfect regioselectivity via an Ir-catalyzed C–H borylation approach.